The Legislative and Regulatory Framework for Plastic Surgery doctors (مجلة الواحات للبحوث والدراسات, 2026)
Cosmetic surgery is considered one of the most prominent surgical procedures performed by people, especially women, as interest in it has increased in recent years. Technological development has helped in the spread of cosmetic surgery greatly. The doctor can choose the appropriate shape for his patient. Thus, he makes him enjoy his beauty because it aims in body reconstruction and restoration, especially if the patient has a congenital deformity or an accident that causes psychological pain. According to the International Plastic Surgery Survey (ISAPS), the number of women undergoing plastic surgery have reached more than 20 million in the world, and is likely to increase dramatically. Most of the legislation was strict with regard to the doctor’s responsibility in plastic surgery, unlike other surgeries. The judiciary recognized plastic surgery as a branch of general surgery in other surgeries. There is strictness regarding determining the obligations of the plastic surgeon, unlike the obligations of the ordinary surgeon.